Implementação e análise do processo interno de seleção de novos diretores do Projeto de Extensão PAC Baja da Universidade Estadual Paulista - Almeida, Giulia Oliveira de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The process of selecting new directors for the PAC Baja Team, an extension project at Universidade Estadual Paulista- Unesp, has always been very troubled and never followed by a standard for recruitment and selection. Through an action-research, a new process to select the new directors was developed and the present work provides a brief account of the implementation and analysis experience of this process.

O processo de seleção de novos diretores da Equipe PAC Baja, projeto de extensão da Universidade Estadual Paulista-Unesp, sempre foi muito conturbado e não seguia um padrão para o recrutamento e seleção. Através de uma pesquisa-ação foi desenvolvido um novo processo de seleção dos novos diretores e o presente trabalho traz um breve relato de experiência da implementação e análise desse processo.
Implementation and analysis of the internal selection process for new directors for the Project of PAC Baja Extension of Universidade Estadual Paulista
Keywords: Internal communication; Talent acquisition; Internal acquisition; Leadership; Comunicação interna; Recrutamento; Pessoal Seleção e admissão; Liderança